2014
DOI: 10.4014/jmb.1407.07063
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Biochemical Characteristics of ��-Propeller Phytase from Marine Pseudomonas sp. BS10-3 and Its Potential Application for Animal Feed Additives

Abstract: Phytate is an antinutritional factor that impacts the bioavailability of essential minerals such as Ca(2+), Mg(2+), Mn(2+), Zn(2+), and Fe(2+) by forming insoluble mineral-phytate salts. These insoluble mineral-phytate salts are hydrolyzed rarely by monogastric animals, because they lack the hydrolyzing phytases and thus excrete the majority of them. The β-propeller phytases (BPPs) hydrolyze these insoluble mineral-phytate salts efficiently. In this study, we cloned a novel BPP gene from a marine Pseudomonas s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In order to reveal the basic characteristics of enzymes and discover novel phytases with desirable properties, the enzyme must be purified and identified. In recent years, a considerable number of phytases have been isolated and cloned in microorganisms, which have achieved heterologous expression, and their enzymatic properties are tested ( Nam et al, 2014 ; Zhang et al, 2015 ; Rix et al, 2021 ). However, the phytases that possess high activity at low temperatures are still uncommon ( Jang et al, 2018 ), which play a role in P cycling and potentially be suitable for use in cold areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to reveal the basic characteristics of enzymes and discover novel phytases with desirable properties, the enzyme must be purified and identified. In recent years, a considerable number of phytases have been isolated and cloned in microorganisms, which have achieved heterologous expression, and their enzymatic properties are tested ( Nam et al, 2014 ; Zhang et al, 2015 ; Rix et al, 2021 ). However, the phytases that possess high activity at low temperatures are still uncommon ( Jang et al, 2018 ), which play a role in P cycling and potentially be suitable for use in cold areas.…”
Section: Discussionmentioning
confidence: 99%
“…The optimal pH of PHY101 was 6.0, stable at pH 5.0–9.0, and the optimum temperature was 40°C, where the temperature is lower than most reported strains of Pseudomonas sp. (50°C) ( Nam et al, 2014 ) and Bacillus sp. (55–60°C) ( Borgi et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…), value slightly higher than the theoretical molecular mass (45.8 kDa). This difference in size might be due to the high content in negatively charged amino acids (18%) (as calculated with ExPASy ProtParam tool, http://web.expasy.org/cgi-bin/protparam/protparam) as suggested by Nam et al and/or post‐translational modifications such as glycosylation that was shown to occur in Streptomyces .…”
Section: Resultsmentioning
confidence: 99%